Tutor Assistance Using The Contextual Teaching And Learning (Ctl) Methods To Improve The Speaking Skills Of Students At The English Language Course Institute Of The Mau Belajar Generation "Gembel" in Samili Village. - Wahyuddin Wahyu; Suryani Suryani (Abdi Masyarakat, 2026)
This PKM activity aims to help tutors improve students' speaking skills by assisting a Contextual Teaching and Learning (CTL) approach. The wrong approach, which gives a chance to student for active both in the study room and outside (outdoor), is the Contextual Teaching And Learning, or called CTL, contextual Method is a draft Study Which make tutor to associate material Which taught with situation real student, pushing students to associate knowledge Which owned with its implementation deep life daily Of environment of family and public. Through the approach, contextual results are more meaningful for the student. This is in line with the theory of Mansur Musical (2008), every component main CTL, have principles base Which must noticed when will apply deep learning, so that approach This If implemented deep learning language English capable increase Ability Speaking. The results of this PKM activity found that the CTL method can provide a positive response in increasing students' willingness to speak through the rules that set aside language errors in terms of both vocabulary and grammar. This is able to minimize students' anxiety in making speaking mistakes, thereby raising motivation to continue speaking in English with confidence and without fear, so that doubts and reluctance to communicate in English can be minimized. However, guidance is still needed for tutors so that the learning process can run well, systematically, and measurably.